GAMBARAN KEMAMPUAN CALON GURU DALAM MENDESAIN MEDIA PEMBELAJARAN FISIKA BERBASIS TEKNOLOGI BERDASARKAN PENDEKATAN TECHNOLOGICAL CONTENT KNOWLEDGE (TCK) - Jannes Bastian Selly (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2023)
ABSTRACT Technological Content Knowledge (TCK) is one of the integrated components of the TPACK approach. TCK is a component that integrates understanding of concepts, principles and theories in certain fields of science, with an understanding of technology so that it can produce fun technology-based learning models or media. The purpose of this study was to determine the description of the ability of prospective teachers in designing appropriate and fun physics learning media. This research is an observational descriptive research with a case study approach. The instruments used in this study were written test questions and observation sheets containing nine TCK indicators. Respondents were asked to work on written test questions on energy material, then respondents were asked to design learning media for the topics studied. The results showed that all respondents (100%) had a good understanding and ability to utilize technology. In contrast, only some respondents (56%) were considered to have a good understanding and ability in the concept of energy. For the TCK integration component, most (74%) received a good assessment from the observer. The results of this study serve as reflection material for efforts to improve the understanding of basic physics concepts for prospective teacher students. Keywords : Technological Knowledge (TK), Content Knowledge (CK), Technological Conten Knowledge (TCK), learning media